1
$\begingroup$

How would you verify that this trigonometric equation is an identity?

$$\sin^4x-\cos^4x=2\sin^2x-1? $$

The 4th powers are really throwing me off, and i'm still fairly new to this and there is no clear identity from the start like $\cos^2x + \sin^2x=1$

Thanks

$\endgroup$
5
$\begingroup$

Hint. You can write $$\sin^4x-\cos^4x=(\sin^2x)^2-(\cos^2x)^2\ ,$$ then use an important factorisation that you would have learned before you ever started trigonometry.

$\endgroup$
3
$\begingroup$

$$\sin^4x-\cos^4x=(\sin^2x-\cos^2x)(\sin^2x+\cos^2x)$$

Now use $\displaystyle \cos^2x + \sin^2x=1$ to eliminate $\cos^2x$

$\endgroup$
3
$\begingroup$

We have that $y^2-(1-y)^2=2y-1$ for any value of $y$. Let $y=\sin^2(x)$ to prove the equality.

$\endgroup$
1
$\begingroup$

Your expression can be written as

$$sin^4x−cos^4x=(sin^2x)^2−(cos^2x)^2$$

so there you 'll get $sin^2 x-cos^2 x$ which is equal to $2sin^2 x -1$. Then the other term is equal to one, which is $sin^2 x +cos^2 x =1$.

So multiply those two terms . Then you will get what you want.

$\endgroup$
0
$\begingroup$

Factor the expression. Remember that $a^2 - b^2 = (a+b)(a-b)$. $$sin^4x + cos^4x$$ $$=(sin^2x)^2 + (cos^2x)^2$$ $$=(sin^2x + cos^2x)(sin^2x - cos^2x)$$ Remember the famous trig. identity $sin^2x + cos^2x = 1$. Using this, you can eliminate that part of the expression from your factoring. $$(sin^2x+cos^2x)(sin^2x-cos^2x)$$ $$=sin^2x-cos^2x$$ You now can use the same identity we used before, $sin^2x + cos^2x = 1$, to rewrite $cos^2x$. We can say that $cos^2x=1-sin^2x$ from simple algebra. This leads to further simplification like so: $$sin^2x-cos^2x$$ $$=sin^2x-(1-sin^2x)$$ $$=sin^2x-1+sin^2x$$ $$=2sin^2x-1$$ Therefore: $$\boxed {sin^4x-cos^4x = 2sin^2x-1}$$ This concludes the proof.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.